1860 Ohio Rev. Stat. 452, ch. 33, §§ 211-212 (Vol. 1) - (:unkn) unknown (My University, 1859)
Be it enacted by the General Assembly of the State of Ohio, that whoever shall carry a weapon or weapons, concealed on or about his person, such as a pistol, bowie knife, dirk, or any other dangerous weapon, shall be deemed guilty of a misdemeanor,
Keywords: CARRY - CONCEALED